Modelagem direta de integrais de domínio usando funções de base radial no contexto do método dos elementos de contorno - Cruz, Átila Lupim (2012)
This research was based on the use of radial basis functions to generate a new integral formulation that interpolates directly the domain action, related to the inhomogeneous term of the governing differential equation, using the Boundary Element Method (BEM). The use of primitive functions of the original interpolation functions in the kernel of the inhomogeneous integral is proposed, allowing its transformation into a boundary integral, thus avoiding the domain discretization through cells, similar to that conducted in the Dual Reciprocity. To better evaluation of the capability of the proposed formulation, the numerical tests presented only solved problems governed by the Poisson Equation. Test problems chosen have known analytical solution, which allowed a better evaluation of the numerical accuracy. To better check the efficiency of the proposed formulation, all the problems were also solved by the Dual Reciprocity Boundary Element Formulation. The computational cost expended for each of these formulations was also compared. Fitting interpolation schemes for both formulations were also tested in order to evaluate their effects on the accuracy of the results and also looking for economy in future computational applications related to wave propagation problems